Trend 1950 - 2004. Center for International Comparisons of Production, Income and Prices. Penn World Table 6.2: Investment Share of PPP Converted GDP per Capita at Current Prices | Country: Iceland, 1950-2004. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 070-002-007. - Center For International Comparisons Of Production, Income (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Center for International Comparisons of Production, Income and Prices (2015). Penn World Table 6.2: Investment Share of PPP Converted GDP per Capita at Current Prices | Country: Iceland, 1950-2004. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 070-002-007. Dataset: Reports the share of real gross domestic product (GDP) per capita that is represented by investment (defined as gross capital formation), using the Geary-Khamis dollar (more commonly known as the international dollar) in current prices. Real GDP in the Penn World Table means GDP converted to international dollars using purchasing power parity (PPP) rates. (An international dollar has the same purchasing power over GDP as a US dollar has in the United States in a given base year, here, 2000.) Current price figures show data where the value for each item is expressed in terms of the prices in that period. The Penn World Table (PWT) displays a set of national accounts economic time series covering many countries. Its expenditure entries are denominated in a common set of prices in a common currency so that real quantity comparisons can be made, both between countries and over time. It also provides information about relative prices within and between countries, as well as demographic data and capital stock estimates. Since the regionalization of the United Nations International Comparison Programme (ICP) beginning with the 1980 benchmark, Robert Summers and Alan Heston at the Center for International Comparisons of Production, Income and Prices at the University of Pennsylvania have been using ICP benchmark comparisons as a basis for estimating PPPs (purchasing power parities) for non-benchmark countries and extrapolations backward and forward in time. The Penn World Tables are described in Summers and Heston "The Penn World Table (Mark 5): An Expanded Set of International Comparisons, 1950-1988" (Quarterly Journal of Economics, May 1991, 327-368). The current version of Penn World Tables, PWT 6.2, was prepared by Bettina Aten, Heston, and Summers with the assistance of Mark McMullen, Feng Zhu, Sham Shah, and Prajesh Parekh and was released in September 2006. V6.2 provides purchasing power parity and national income accounts converted to international prices for 188 countries, 1950-2004, where available, with 2000 as the reference year. PWT 6.2 combines 2002 benchmark data for 30 Organisation for Economic Co-operation and Development countries, updates for the other 138 countries in PWT 6.1, and adds 20 additional countries. Category: Industry, Business, and Commerce, International Relations and Trade Source: Center for International Comparisons of Production, Income and Prices The Center for International Comparisons of Production, Income and Prices at the University of Pennsylvania (CICUP) was established in 1990 to continue an intellectual tradition begun at Penn during the 1940s by Simon Kuznets. Kuznets was on the faculty and was further elaborating the system of national accounts that he had helped create. Irving B. Kravis, a student of Kuznets’, moved forward research in the area of spatial national accounts, first with his work for the Organization for European Economic Cooperation with Milton Gilbert. Another Kuznets student, Richard Easterlin, engaged in a number of historical studies of the regional growth of the United States economy. CICUP was established as a center that would include these traditions in addition to other areas of research involving cross-country and inter-area comparisons of incomes and prices. https://pwt.sas.upenn.edu/ Subject: Purchasing Power, Investments, Gross Domestic Product (GDP), Social Development, Economic Development